Multi-Program Strategy For Waste Managemen In Argo Mulyo Village: Socialization Of Waste Sorting, Waste Banks And Eco-Enzyme Production - Elvira Anggraeni, Angelica (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background: The production of organic and inorganic waste is quite large every day, especially waste originating from household waste. Organic waste is a type of waste that comes from natural materials that can decompose naturally, for example food waste, fruit peels, vegetable waste, dry leaves and the like. Meanwhile, inorganic waste is waste that comes from non-natural materials or materials that do not easily decompose naturally, for example plastic, cans, paper and the like. Meanwhile, B3 waste has dangerous and toxic properties for humans and the environment, for example used batteries, lamps and chemical waste. Therefore, waste sorting is a crucial first step in efforts to reduce the negative impact of waste on the environment and public health. Proper waste sorting by knowing the types of waste in the household allows for more efficient waste handling and opens up opportunities for recycling and reuse. The problem of accumulation of household waste, especially organic waste in the domestic environment, is still a big problem, because the level of public awareness of the importance of good organic waste management is still relatively low. Objective : to increase residents' knowledge regarding sorting household waste and processing it into something useful Research Methods/ Implementation Methods : The method is carried out by introducing the community, recognizing the problem, solving the problem, implementing the program and evaluating at the final stage Results : From the procedure above, it was found that the problem in Argo Mulyo village was waste, which was then carried out by FGD with the factors causing the problems being related to the absence of TPS. so that from this problem, intervention programs were created in the form of